Optimal orientation of phase change material energy storage systems for different performance indicators and charging levels - Reda Ameen; ELSaeed Saad ELSihy; Mohamed Shedid; Hosny Abou-Ziyan (Case Studies in Thermal Engineering)
This paper establishes the contradictory relationship between the storage orientation and both the charging levels and the performance indicators of single-stage latent heat thermal energy storage systems (LHTESS). The performance indicators (cycle charging capacity, charging time, charging rate, and average effectiveness) at seven inclination angles (0, 15, 30, 45, 60, 75, and 90°) and six charging levels (0.5, 0.7, 0.9, 0.98, 0.99, and 1.0) are obtained. A three-dimensional transient simulation model based on the enthalpy porosity technique is developed to evaluate the LHTESS performance. The results showed that the best inclination angle for the single-stage LHTESS is strongly related to the charging level and the considered performance indicator. The charging time and charging rate are more sensitive to the orientation and charging level than the effectiveness or cyclic charging capacity. Conversely, the maximum cycle charging capacity is independent of the charging level, as it always occurs with the horizontal LHTESS. At the complete charging level, the lowest charging time, the highest charging rate, and average effectiveness happen at an inclination angle of 60°. In contrast, the highest charging rate occurs at inclination angles of 15, 30, 45, and 60° at charging levels of 0.50, 0.70–0.90, 0.98–0.99, and 1.0, respectively. Also, the highest average effectiveness occurs for the horizontal LHTESS at liquid fractions of 0.50 and 0.70, 30° for a liquid fraction of 0.90, and 45° for liquid fractions of 0.98 and 0.99.